2021
DOI: 10.1007/s00262-021-03064-6
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint CD155 promoter methylation profiling reveals cancer-associated behaviors within breast neoplasia

Abstract: BACKGROUND: CD155 immune checkpoint has recently emerged as a compelling immunotherapeutic target. Epigenetic DNA methylation changes are recognized as key molecular mechanisms in cancer development. Hence, the identification of methylation markers that are sensitive and specific for breast cancer may improve early detection and predict prognosis. We speculate that CD155 promoter methylation can be a valuable epigenetic biomarker, based upon strong indications for its immunoregulatory functions.METHODS: Methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…28,32 Moreover, the researchers found that the methylation at the CpG site of the CD155 promoter is directly related to cancer progression and tumor size. 33 However, there is little information about the role of this biomarker (CD155) in breast cancer. 34 Our findings revealed that the expression of this biomarker increases in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…28,32 Moreover, the researchers found that the methylation at the CpG site of the CD155 promoter is directly related to cancer progression and tumor size. 33 However, there is little information about the role of this biomarker (CD155) in breast cancer. 34 Our findings revealed that the expression of this biomarker increases in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on hepatocellular carcinoma, LOXL3 was first reported to link with immune infiltrates. A statistical analysis has been applied to explore the relationship between the LOXL3 expression and the infiltration of multiple immune cells ( Wang N. et al, 2021 ; Triki et al, 2022 ). The association between target gene and immune-cell infiltration can be further verified experimentally, with quantitative multiplex immunohistochemistry or immunohistochemistry staining ( Wang Y. et al, 2021 ; Gatti et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%